Fe nanoparticles embedded in polyaniline-derived carbon fibers as broad bandwidth microwave absorbers for GHz electromagnetic wave. (August 2021) - Su, Shaohui; Yu, Jiahao; Liu, Xianguo; Yu, Jieyi
Abstract: Magnetic-dielectric composites attract numerous attentions for good microwave absorption performances based on magnetic-dielectric loss mechanism and tunable electromagnetic parameters. Fe/carbon fibers are prepared through carbonization of Fe doped polyaniline nanotubes, in which Fe nanoparticles are embedded in carbon fibers. The introduction of Fe nanoparticles results in good electromagnetic impedance and proper quarter-wavelength cancellation induced, which ensure that microwave penetrate composites to the great extend and is consumed as much as possible, leading to enhanced microwave absorption performance. The minimal reflection loss of Fe/carbon fibers composites starts being less than −10 dB from 1.7 mm and is up to −44.09 dB at 6.62 GHz and 4.1 mm and the effective bandwidth reaches 6.0 GHz with 2.4 mm. Highlights: Fe/carbon fibers composites are synthesized by the carbonization of Fe-doped PANI nanotubes. The co-doping of S and N atom has no influence on magnetic loss, but improves dielectric loss ability. The addition of Fe nanoparticles leads to proper impedance match, making more microwave into PANI. The Fe-CF composites possess RL max of-44.09 dB at 6.62 GHz and f E of 6 GHz at 2.4 mm.